Habitat-specific constraints on induced hatching in a treefrog with reproductive mode plasticity (2011)
ABSTRACT: Many organisms show adaptive phenotypic plasticity in response to environmental variation. Some environmental factors may, however, impose constraints on the ability of organisms to respond to other factors. The neotropical treefrog Dendropsophus ebraccatus lays eggs both above water on leaves and directly in water, thereby exposing embryos to different abiotic conditions and predator communities. Rising pond levels can also flood arboreal clutches after rainstorms. We tested for predator-induced hatching in submerged and arboreal D. ebraccatus egg masses and assessed effects of prior hydration or desiccation on escape success in attacks by a terrestrial predator, Azteca ants, and an aquatic predator, large conspecific tadpoles. Embryos responded to both aquatic and terrestrial predator attacks by hatching prematurely, as much as 67% earlier than the peak of hatching in undisturbed clutches. Desiccation reduced the hatching response of terrestrial embryos, resulting in substantially lower escape rates. This desiccation effect disappeared rapidly with flooding; all embryos showed high escape hatching success underwater. The occurrence of predator-induced escape hatching in response to 2 different predators, in 2 different physical environments, suggests that this is a general response of D. ebraccatus to egg predator attack. Both ant attack and sublethal desiccation are common in nature, thus the inhibition of escape hatching in this context likely impacts tadpole recruitment. More generally, we demonstrate that an adaptive plastic response to risk is contingent on additional environmental variables and suggest that many instances of plasticity may similarly be modified by environmental constraints.